Mediators of the sacred: native auxiliaries of the Jesuit Missionaries in the Western Amazon (c. 1638-1767) - Carvalho, Francismar Alex Lopes de (Revista de História, 2015)
This article analyzes indigenous participation in the expansion of the Christian doctrine in western Amazonian Jesuit missions. When starting a reduction, Jesuits usually trained some chiefs to serve as catechists. Over time, Jesuits educated the sons of indigenous leaders and chose some of the children of common and captive Indians to form a select group of “prosecutors of the doctrine” (fiscales de doctrina), sextons, and musicians. Priests also encouraged the establishment of confraternities in which only virtuous and devout Indians could participate. This article focuses on the Spanish Jesuit missions of Maynas, Mojos and Chiquitos. I argue that by relying on indigenous agents to facilitate the translation of Christian doctrine to neophytes, Jesuits could not completely banish certain practices and representations that ensured the legitimacy of their mediators.